Application of paclitaxel in low non-cytotoxic doses supports vaccination with melanoma antigens in normal mice - Sevko, Alexandra; Kremer, Veronika; Umansky, Ludmila; Umansky, Viktor (Journal of immunotoxicology, 2012)
Chemotherapeutic agents such as paclitaxel applied in ultra-low, non-cytotoxic doses were previously shown to stimulate dendritic cell activity and anti-tumor immune responses upon vaccination in mouse transplantable tumor models. However, the mechanisms of these alterations-termed chemoimmunomodulation or chemomodulation-are still not clear. This study investigated the effect of paclitaxel applied in ultra-low, non-cytotoxic doses on the efficiency of immunization of healthy C57BL/6 mice with the peptide derived from tyrosinase related protein (TRP)-2 as a model melanoma antigen. Using an IFNγ ELISPOT assay, it was found that administration of 1 mg paclitaxel/kg in combination with the peptide vaccination strongly increased the frequencies of TRP-2 specific spleen T-cells as compared to levels due to the vaccination alone. This was associated with a significant decrease in the levels of regulatory T-cells (Treg) and immature myeloid cells (known as a counterpart of myeloid derived suppressor cells [MDSC] in healthy mice). Such impairments of potential immunosuppressive cells were found to correlate with a strong increase in the amount of effector CD8+ and CD4+ T-cells in the bone marrow and spleen. Furthermore, in paclitaxel-treated mice, a significant augmentation of natural killer (NK) cell numbers in the bone marrow and their ability to produce IFNγ were observed. In addition, the level of NK-T-cells in the lymph nodes was also increased. It is suggested that paclitaxel applied in ultra-low, non-cytotoxic doses may potentially enhance the efficacy of anti-tumor vaccinations by neutralizing immunosuppressive Treg and MDSC populations in tumor-bearing hosts.
Published online: 27 Mar 2012
Gesehen am 16.07.2018